The effects of ranibizumab (Lucentis) on retinal function in isolated perfused vertebrate retina. Issue 10 (23rd July 2009) - Lüke, M; Januschowski, K; Lüke, J; Peters, S; Wirtz, N; Yörük, E; Lüke, C; Bartz-Schmidt, K U; Grisanti, S; Szurman, P
Abstract : Background: Intraocular ranibizumab (Lucentis, Novartis, Basel Switzerland) is the primary choice in the treatment of neovascular age-related macular degeneration (AMD). Vascular endothelial growth factor (VEGF) is known to be a survival factor for neuronal cells. Therefore, blockage of all VEGF isoforms by ranibizumab could induce retinal dysfunction. Methods: Using isolated bovine retinas, the electroretinogram (ERG) was recorded as a transretinal potential using Ag/AgCl electrodes, while the retinas were perfused with an oxygen preincubated nutrient solution. For 45 min, ranibizumab was applied at a concentration of 0.2 mg/ml and alternatively the solvent carrier without the active agent. The ERG was monitored before, during and after exposure. Results: The concentration of 0.2 mg/ml ranibizumab induced a non-significant b-wave reduction of 22.32% after exposure (p = 0.13). For the a-wave amplitude only a reduction of 4% was detected (p = 0.18). The solvent carrier induced no significant reduction of the a- and b-wave amplitudes (p = 0.30 and p = 0.979, respectively). Conclusion: In the ex vivo model, the isolated perfused vertebrate retina, ranibizumab has been proven to be a safe compound at the concentrations applied. The stability of the ERG-amplitudes rules out a considerable retinal dysfunction after an injection of up to 1 mg ranibizumab.